Design and Optimization of an Automated Ceramic Drying System Using Arduino for Small and Medium Enterprises - Muchamad Sugarindra; Arifa, Dhinar Elma; Parkhan, Ali (Advance Sustainable Science Engineering and Technology, 2026)
The ceramic drying process in Small and Medium Enterprises (SMEs) often relies on ambient conditions, leading to prolonged drying times and inconsistencies in product quality. This study presents the design and optimization of an automated ceramic drying system that utilizes an Arduino-based microcontroller to regulate temperature and airflow in real-time. A full factorial experimental design was employed to investigate the influence of two critical parameters—temperature (35°C, 40°C, 45°C) and air velocity (3 m/s, 4 m/s, 5 m/s)—on drying performance. Experimental results identified the optimal condition at 45°C and 3 m/s, yielding the shortest drying time of 18.031 seconds. Statistical analysis using ANOVA confirmed the significance of temperature (F = 34.69, p = 0.002) and air velocity (F = 6.97, p = 0.044), with temperature accounting for 78.87% of the total variation. Furthermore, Signal-to-Noise Ratio (SNR) analysis based on the Smaller-the-Better criterion validated the robustness of the optimal settings. The proposed system offers SMEs a low-cost, scalable, and reliable solution, enabling improved drying efficiency, enhanced product quality, and reduced process variability through accessible automation technologies.